Recurrent hemorrhage from corpus luteum during anticoagulant therapy - Wong, K. P.; Gillett, P. G. (CMAJ, 1977)
A 43-year old woman had recurrent massive intraperitoneal hemorrhage from rupture of a hemorrhagic corpus luteum in two successive menstrual cycles while receiving anticoagulant therapy. Left oophorectomy was performed on the first occasion and right salpingo-oophorectomy with left salpingectomy on the second. While the precise incidence cannot be determined, rupture from a hemorrhagic corpus luteum appears to be a rare but potentially catastrophic complication of anticoagulant therapy. Hence possible ovarian hemorrhage should be considered in women of reproductive age receiving heparin or sodium warfarin therapy.